Causative factors of Abandoned Urban Housing Projects and Strategies for Revitalization in Ibadan, Nigeria - Obakin, Olufunmilola Adetayo; Afolami, Samuel Kehinde; Akande, Oluwafemi Kehinde (Alanya Üniversitesi, 2024)
In Nigeria, over 56,000 projects have been abandoned, leading to negative societal and urban impacts, including wasted investment, job losses, increased crime rates, visual pollution, and disruption of urban planning. These abandoned projects, which include residential, commercial, and industrial buildings, have significant multiplier effects on the construction industry. As the housing sector plays a vital role in a country's economy, the issue of abandoned urban housing projects, particularly in Ibadan, Nigeria’s third-largest city, poses serious challenges. These challenges affect the city’s economic growth, social cohesion, and environmental quality, yet there is limited research addressing the problem. This paper investigated the causes of abandoned housing projects in Ibadan, aiming to find ways to revive them and prevent future abandonment. A structured questionnaire (n=45) was administered to consultants and professionals in the built environment (architects, engineers, quantity surveyors, and builders). Key causes of abandonment were identified, along with impacts such as building dilapidation, environmental decline, and urban visual displeasure. The paper recommended the establishment of regulatory frameworks for periodic inspections of ongoing projects and requiring developers to have exit strategies for financial setbacks. It also emphasized policies that promote repurposing abandoned buildings for public services, such as affordable housing or community centers. The conclusion stressed that without addressing the root causes, urban aesthetics and adequate housing provision will continue to suffer.